Penerapan Bimbingan Karir untuk Meningkatkan Bakat dan Minat - Friska Martha Bella Ambar Sari; Arifin Nur Budiono; Azizah Aziz (Program Studi Bimbingan dan Konseling FKIP Universitas Islam Jember, 2019)
Application of Career Guidance to increase Talent and Interest of students in MA’ARIF13 Middle School Curahtakir Tempurejo Jember Regency.Research on the Application of Career Guidance to increase Talent and Interest of students at MA'ARIF Middle School 13 Curahtakir Tempurejo, Jember Regency with the respondents studied were 32 students. The methods used in this study were Observation, Reflection and Questionnaire.Based on preliminary research results obtained data with a percentage number (37%) which is 12 students in the high value category, (63%) which is 20 students in the moderate value category and there are no students in the low value category, after being given action in cycle I the application of career guidance to improve the talents and interests of students has increased with the percentage (81%) that is 26 students in the high value category, (19%) that is 6 students in the medium category and not found in the low value category.Thus concluded:the application of career guidance to increase students' talent, has increased. Research activities are categorized as successful because they reach a percentage above the success indicator which is set at 75% of students get or are in the high value category.In this thesis also provides suggestions for the perfection of further research and the closing is the end of this thesis research report. Keywords: Career Guidance, Talents and Interests